Ethnic differences in breast cancer incidence in England are due to differences in known risk factors for the disease: Prospective study - Gathani, T; Ali, R; Balkwill, A; Green, J; Reeves, G; Beral, V; Moser, K (2014)
Background:In the United Kingdom, breast cancer incidence is lower in South Asian and Black women than in White women, but the extent to which this is due to known risk factors is unknown. In a large prospective study, we describe breast cancer incidence by ethnicity, before and after adjustment for known risk factors for the disease.Methods:Women were recruited into the Million Women Study in 1996-2001, when information on reproductive and lifestyle factors known to influence the risk of breast cancer was obtained. Ethnicity was determined from study questionnaires and hospital admission data. Cox regression models were used to calculate adjusted relative risks (RR) for incident breast cancer in South Asians and Blacks compared with Whites.Results:Analyses included 5877 South Asian, 4919 Black, and 1 038 144 White women in England. The prevalence of 8 out of the 9 risk factors for breast cancer examined, differed substantially by ethnicity (P<0.001 for each), such that South Asian and Black women were at a lower risk of the disease than White women. During 12.2 years of follow-up incident breast cancer occurred in 217 South Asians, 180 Blacks, and 45 191 Whites. As expected, breast cancer incidence was lower in South Asians (RR=0.82, 95% CI 0.72-0.94) and Blacks (RR=0.85, 0.73-0.98) than in Whites when the analyses were adjusted only for age and region of residence. However, after additional adjustment for the known risk factors for the disease, breast cancer incidence was similar to that of Whites, both in South Asians (0.95, 0.83-1.09) and in Blacks (0.91, 0.78-1.05).Conclusion:South Asian and Black women in England have lower incidence rates of breast cancer than White women, but this is largely, if not wholly, because of differences in known risk factors for the disease. © 2014 Cancer Research UK.